Marketing Strategy for Processed Chili Products "Sambal Simbok" Tuna Sambal Variant in Ambulu, Jember - Kustiari, Tanti; Kinanti, Lintang Anis Bena; Astutik, Diar Fidi (Journal of Agriculture, 2023)
Red chili (Capsicum annuum) is a leading horticultural commodity that is perishable and seasonal, so it must be sold immediately after being harvested. To extend its lifespan and durability, processing is required which of course requires additional costs. Marketing processed products in the era of globalization of trade includes various challenges which should be interpreted as opportunities to be able to compete in international markets. KWT LARASATI took the initiative to process large red chilies in order to increase the added value of the harvest and also extend its shelf life. From this process, KWT LARASATI then produces high-value product diversification in the form of processed chili sauce under the Sambal Simbok brand. One variant of the chili sauce produced is tuna chili sauce. So far, KWT LARASATI has carried out marketing techniques in the form of utilizing existing social media, namely WhatsApp, Facebook and Instagram. However, KWT Larasati still faces a number of obstacles in marketing its Sambal Simbok tuna chili variant to the public. Based on this background, it is necessary to have a strategy in marketing the Sambal Simbok product, a tuna chili variant so that it can produce alternative strategies that suit the processed chili products in KW LARASATI business diversification, as well as using QSPM analysis to determine strategic priorities that are in accordance with internal and external aspects. KWT. The results of this analysis are eight alternative strategies which are then ranked to determine the prioritized strategy.